Analisis Perkembangan Kognitif, Motorik, dan Sosial-Emosional Anak Usia Dini (0–2 Tahun) dalam Masa Golden Age - Caroline Rotua Joesputri Samosir Samosir; Asep Yogie Sholihin; Laila Puspita; Shifa Aulia Sabna; Lisna Maulia; Wina Mustikaati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the cognitive, motor, and socio-emotional development of early childhood (0–2 years) during the golden age period. The research uses a qualitative approach through observation and literature review techniques. The results show that children aged 0–2 years experience rapid development in cognitive, motor, and socio-emotional aspects. Cognitive development is characterized by the ability to recognize the environment through sensorimotor interactions, motor development is reflected in the improvement of gross and fine motor skills, while socio-emotional development is indicated by children’s responses to their environment and interactions with others. Furthermore, appropriate stimulation from the environment, especially from parents, plays a crucial role in supporting optimal child development. Without adequate stimulation, children may experience developmental delays. Therefore, understanding the golden age period is essential, particularly for parents and prospective educators, to provide appropriate and optimal stimulation for early childhood development.